2010
DOI: 10.1063/1.3469799
|View full text |Cite
|
Sign up to set email alerts
|

A new absolute extreme ultraviolet image system designed for studying the radiated power of the Joint Texas Experimental Tokamak discharges

Abstract: A bolometer imaging system mounted on different toroidal and poloidal locations used for radiation observation has been developed in the Joint Texas Experimental Tokamak (J-TEXT tokamak). Three miniature pinhole AXUV16ELG (16 elements absolute extreme ultraviolet silicon photodiodes) array cameras, which are settled down in the same toroidal position but in three different poloidal places, can provide a broad viewing angle that covers the whole plasma cross-section, and hence can measure the total radiated pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Here gives the estimated impurity assimilation rate η=38% in red dashed line based on the pressure balance η=N imp /N inj = V plasma T inj /V vaccum T imp when using the assumption T imp = T inj , where N inj , T imp , T inj , and V vaccum are the total injected impurity quantity, the temperature of the ionized impurity in the RE plasma, the temperature of the neutral impurity, and the volume of the vacuum vessel respectively. It can be found that the maximum assimilation rate η of the krypton impurity can fit the estimated impurity assimilation rate 38% when the total injected impurity quantity is lower than 2×10 21 . Then the assimilation rate η decreases when the injected impurity quantity is larger than 2×10 21 .…”
Section: Impurity Assimilation During Runaway Current Dissipation Phasementioning
confidence: 92%
See 3 more Smart Citations
“…Here gives the estimated impurity assimilation rate η=38% in red dashed line based on the pressure balance η=N imp /N inj = V plasma T inj /V vaccum T imp when using the assumption T imp = T inj , where N inj , T imp , T inj , and V vaccum are the total injected impurity quantity, the temperature of the ionized impurity in the RE plasma, the temperature of the neutral impurity, and the volume of the vacuum vessel respectively. It can be found that the maximum assimilation rate η of the krypton impurity can fit the estimated impurity assimilation rate 38% when the total injected impurity quantity is lower than 2×10 21 . Then the assimilation rate η decreases when the injected impurity quantity is larger than 2×10 21 .…”
Section: Impurity Assimilation During Runaway Current Dissipation Phasementioning
confidence: 92%
“…The total radiated power is calculated by using the A and D arrays of the No.1 AXUV imaging subsystem at port 3. The calculation method is shown in the [21]. The polarizing interferometer (named as POLARIS on J-TEXT) with 17 vertical chords is used to measure the electron density profile [22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another nine AXUV10EL (ten elements) array cameras are divided into three groups and mounted at different toroidal locations to observe the toroidal radiated power distribution. The AXUV array has a sensitivity from 0.20 to 0.27 A W −1 for photon energies of 25 eV-6 keV and has a temporal resolution of 20 µs [13]. (6) A spectrometer with 2400 lines mm −1 grating is used to record the emission spectrum from 200 to 1100 nm along a vertical centre chord through the plasma.…”
Section: Development Of Diagnostic Systemsmentioning
confidence: 99%